Screening for ROS1 gene rearrangements in non‐small‐cell lung cancers using immunohistochemistry with FISH confirmation is an effective method to identify this rare target. Issue 3 (15th November 2016) - Selinger, Christina I; Li, Bob T; Pavlakis, Nick; Links, Matthew; Gill, Anthony J; Lee, Adrian; Clarke, Stephen; Tran, Thang N; Lum, Trina; Yip, Po Y; Horvath, Lisa; Yu, Bing; et al.
Abstract : Aims: To assess the prevalence of ROS1 rearrangements in a retrospective and prospective diagnostic Australian cohort and evaluate the effectiveness of immunohistochemical screening. Methods and results: A retrospective cohort of 278 early stage lung adenocarcinomas and an additional 104 prospective non‐small‐cell lung cancer (NSCLC) cases referred for routine molecular testing were evaluated. ROS1 immunohistochemistry (IHC) was performed (D4D6 clone, Cell Signaling Technology) on all cases as well as fluorescence in‐situ hybridization (FISH) using the ZytoVision and Abbott Molecular ROS1 FISH probes, with ≥15% of cells with split signals considered positive for rearrangement. Eighty‐eight cases (32%) from the retrospective cohort showed staining by ROS1 IHC, and one case (0.4%) showed ROS1 rearrangement by FISH. Nineteen of the prospective diagnostic cases showed ROS1 IHC staining, 12 (12%) cases of which were confirmed as ROS1 rearranged by FISH. There were no ROS1 rearranged cases that showed no expression of ROS1 with IHC. The ROS1 rearranged cases in the prospective cohort were all EGFR wild‐type and anaplastic lymphoma kinase ( ALK ) rearrangement‐negative. The sensitivity of ROS1 IHC in the retrospective cohort was 100% and specificity was 76%. Conclusions: ROS1 rearrangements are rare events in lung adenocarcinomas. Selection of cases for ROS1 FISH testing, by excluding EGFR/ALK ‐positive cases and use of IHC to screen for potentially positive cases, can be used to enrich for the likelihood of identifying a ROS1 rearranged lung cancer and prevent the need to undertake expensive and time‐consuming FISH testing in all cases.